International Tax Planning: The Concept of Place of Effective Management - Goosen, Chantelle (Department of Commercial Law, 2014)
This dissertation will study certain aspects of the South African Income Tax Act2 such as residence-based concepts, with specific reference to place of effective management, which brings a taxpayer within the ambit of the South African Tax Law. It will also address issues regarding Double taxation agreements and the impact of all these issues on companies trading internationally. This paper is intended to raise an awareness of the current issues, general principles and practices to be taken into account when organizing a company's affairs to limit the tax liability in South Africa.